A comparison of panoramic views reformatted from CBCT scans using manual or automated workflows: an evaluation of geometric accuracy and subjective image quality - Ali Fahd; Mohamed T. Ellabban; Michael M. Bornstein; Ola M. Rehan (Clinical Oral Investigations, 2026)
Abstract Objectives This study aimed to compare (1) the geometric accuracy and (2) subjective image quality of CBCT reformatted panoramic images generated using three reconstruction workflows: automatic reconstruction, nasal spine plane-oriented manual reconstruction, and occlusal plane-oriented manual reconstruction. Materials and methods Twenty-eight CBCT datasets were included. Three panoramic reconstruction protocols were assessed. Linear measurements were obtained on axial images (as a reference) and on the corresponding reformatted panoramic images. Measurements included (for geometric accuracy): mesiodistal crown width of a selected maxillary central incisor; inter-radicular distance at the alveolar crest between adjacent anterior teeth; and panoramic interslice distance (PISD), defined as the distance between the primary panoramic line (center of the panoramic curve) and the secondary panoramic line at the measurement site. A 7-item binary visual scoring system was used to compare subjective image quality across protocols. Results Crown-level measurements differed significantly between axial images and reformatted panoramic images across all protocols. Bone-level measurements showed significant differences in G1 and G3, while there was no significant difference in the G2 protocol. In all groups, measurement error (absolute and percentage) showed a significant positive correlation with PISD. Subjective image quality scores differed across protocols. Conclusions CBCT-reformatted panorama demonstrated protocol-dependent differences for linear measurements and subjective image quality. Measurement errors increased as the measurement sites deviated from the center of the drawn panoramic curve. Clinical Relevance Reformatted panorama requires cautious interpretation and should not be relied upon for precise quantitative assessments. Cross-verification with other views is essential before definitive clinical decisions.